Nutritional ketosis improves exercise metabolism in patients with very long-chain acyl-CoA dehydrogenase deficiency - Bleeker, JC; Visser, G; Clarke, K; Ferdinandusse, S; de Haan, FH; Houtkooper, RH; IJlst, L; Kok, IL; Langeveld, M; van der Pol, WL; de Sain-van der Velden, MGM; Sibeijn-Kuiper, A; et al. (Wiley, 2020)
A maladaptive shift from fat to carbohydrate (CHO) oxidation during exercise is thought to underlie myopathy and exercise‐induced rhabdomyolysis in patients with fatty acid oxidation (FAO) disorders. We hypothesised that ingestion of a ketone ester (KE) drink prior to exercise could serve as an alternative oxidative substrate supply to boost muscular ATP homeostasis. To establish a rational basis for therapeutic use of KE supplementation in FAO, we tested this hypothesis in patients deficient in Very Long‐Chain acyl‐CoA Dehydrogenase (VLCAD). Five patients (range 17‐45 y; 4 M/1F) patients were included in an investigator‐initiated, randomised, blinded, placebo‐controlled, 2‐way cross‐over study. Patients drank either a KE + CHO mix or an isocaloric CHO equivalent and performed 35 minutes upright cycling followed by 10 minutes supine cycling inside a Magnetic Resonance scanner at individual maximal FAO work rate (fatmax ; approximately 40% VO2max). The protocol was repeated after a 1‐week interval with the alternate drink. Primary outcome measures were quadriceps phosphocreatine (PCr), Pi and pH dynamics during exercise and recovery assayed by in vivo 31P‐MR spectroscopy. Secondary outcomes included plasma and muscle metabolites and respiratory gas exchange recordings. Ingestion of KE rapidly induced mild ketosis and increased muscle BHB content. During exercise at FATMAX, VLCADD‐specific plasma acylcarnitine levels, quadriceps glycolytic intermediate levels and in vivo Pi/PCr ratio were all lower in KE + CHO than CHO. These results provide a rational basis for future clinical trials of synthetic ketone ester supplementation therapy in patients with FAO disorders.